Peran Program Wirausaha Merdeka dan Magang Kewirausahaan dalam Meningkatkan Jiwa dan Kompetensi Kewirausahaan Mahasiswa - Rendi Wahyu Saputra; Sitti Retno Faridatussalam (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The Independent Entrepreneurship Program is one of the strategic efforts of the Ministry of Education, Culture, Research, and Technology in fostering the entrepreneurial spirit of students through direct experiential learning. This program is present as a forum for students to not only understand entrepreneurship theory, but also to practice in real life the process of building and managing a business. In its implementation, the program involves active collaboration between universities, industry mentors, and field supervisors who play a role in providing direction, guidance, and evaluation of student business development. Through Independent Entrepreneurship, students are given the opportunity to design creative business ideas, run a business on a real scale, and solve various entrepreneurial challenges they face. This activity not only trains managerial, communication, and innovation skills, but also improves critical thinking and problem-solving skills. In addition, students gain valuable experience in terms of teamwork, financial management, marketing strategies, building business networks, and the use of digital technology to support business sustainability. The results of the program implementation show positive impacts, including increased confidence, independence, and students' understanding of the real business world. Furthermore, this program encourages the creation of an entrepreneurial ecosystem in a sustainable campus environment and is able to be the forerunner of the birth of a young generation of Indonesian entrepreneurs who are resilient, innovative, creative, adaptive to changing times, and have high competitiveness. Thus, Independent Entrepreneurship not only plays a role as a skill development program, but also becomes one of the important foundations in preparing students to face the world of work and becoming independent business actors who are professional, visionary, sustainability-oriented, and make a real contribution to the nation's economic development.